The Effect of Flammulina velutipes Polysaccharide on Immunization Analyzed by Intestinal Flora and Proteomics - Liang, Qiongxin; Zhao, Qingchun; Hao, Xuting; Wang, Jinmei; Ma, Changyang; Xi, Xuefeng; Kang, Wenyi (Frontiers in Nutrition, 2022)
Proteomics and intestinal flora were used to determine the mechanism of immune modulatory effects of Flammulina velutipes polysaccharide on immunosuppressed mice. The results showed that compared with the model group, F. velutipes polysaccharide could increase thymus and spleen indices and improve thymus tissue structure in mice; IL-2 and IL-4 contents were significantly increased and IL-6 and TNF-α contents were significantly decreased; serum acid phosphatase (ACP), lactate dehydrogenase (LDH) and total antioxidant capacity (T-AOC) activities were increased (P < 0.05); in the liver, superoxide dismutase (SOD) and catalase (CAT) activities were increased (P < 0.001), while malondialdehyde (MDA) content was decreased (P < 0.001). Proteomics discovered that F. velutipes polysaccharides may exert immune modulatory effects by participating in signaling pathways such as immune diseases, transport and catabolism, phagosomes and influenza A, regulating the immune-related proteins Transferrin receptor protein 1 (TFRC) and Radical S-adenosyl methionine domain-containing protein 2 (RSAD2), etc. Gut microbial studies showed that F. velutipes polysaccharides could increase the abundance of intestinal flora and improve the flora structure. Compared to the model group, the content of short-chain fatty acids (SCFAs) and the relative abundance of SCFA-producers Bacteroides and Alloprevotella were increased in the F. velutipes polysaccharide administration group, while Lachnospiraceae_NK4A136_group and f_Lachnospiraceae_Unclassified decreased in relative abundance. Thus, F. velutipes polysaccharide may play an immunomodulatory role by regulating the intestinal environment and improving the balance of flora.